Pengaruh Mengerjakan Skripsi terhadap Tingkat Stress pada Mahasiswa Tingkat Akhir - Andari Elyana Maharani; Chandra Putri Kharisma; Fairuz Salsabila (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Students are at the limit of late adolescence and early adulthood, where this period is a period of unstable mental conditions, accompanied by conflicts and demands as well as changes in mood. For final year students, what often becomes a stressor is completing their thesis. Symptoms of stress in students are feeling tired, anxious, not enthusiastic or wanting to stop working on their thesis. The impact is that work on the thesis is postponed and people choose to forget it, avoid their supervisors, complain on social media about the difficulties they face and ultimately the study period is delayed. This research aims to determine the effect of writing a thesis on mental health and stress levels in students. The research uses qualitative methods with survey research via Google Form.